Peran Mahasiswa sebagai Agent of Change dalam Implikasi dan Penerapan Nilai-Nilai Pancasila di Kehidupan Bermasyarakat - Agus Hidayat, Agus Hidayat (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2025)
Pancasila, as the national ideology of Indonesia, plays a crucial role in shaping the character and behavior of society. However, in recent decades, the implementation of Pancasila's values has faced significant challenges due to social inequalities and the impacts of globalization. Social and cultural changes brought about by globalization, such as individualism and hedonism, threaten the core principles of Pancasila, such as mutual cooperation, tolerance, and social justice. As the next generation, students are expected to become agents of change by implementing the values of Pancasila in society. However, despite the principles of Pancasila being outlined in various policies, many practices still contradict these values. Therefore, there is a need for greater efforts to instill a deeper and more practical understanding of Pancasila in order to create a harmonious, just society in accordance with the guidelines of Pancasila. Keywords: Students, Agents of Change, Implementation of Pancasila, Social Life